A mediação e o "pensar alto em grupo": caminhos para o desenvolvimento da leitura crítica - Silva, Maria das Graças Bouças da (2008)
This research intends to investigate, by means of an action-research of ethnographic character, the language teaching and learning process of critical reading and the role of mediation for this process, in an eight grade group. Theoretically, this research is based on a) the vygotskian approach, according to which in the learning process the other person (receiver) and the language itself have important roles as mediators of language teaching and learning process; b) the perspective of reading as a social practice and c) the metaphor. The date a to be analysed were collected by using two media: 1) verbal protocols in group or think-aloud in group (Zanotto, 1997) and; 2) reflexive diaries, made during some meetings along the year of 2006, in a public school of Itaquaquecetuba, in São Paulo. The data that were analysed inquired: the teacher s or partner s contribution for critical reading development; the possible contributions of the metaphor for construction of the meaning of the text and, at last, the contributions of the verbal protocols or think-aloud in group in teaching and learning development. The results revealed that the mediation of the teacher or of a classmate made the critical reading become easier. It was also shown that the metaphor had the role of a mediator in the building of senses of the text and the verbal protocol, as a teaching tool, contributed for the change in pupils attitude towards reading some printed matter. Regarding the development of ability of critical reading, which was one of the aims of this research, it is possible to say that the pupils are just beginning in the process of becoming critical readers, and this may be the result of many years of school activities and also out of school. Besides that it is necessary that the teacher uses those educational practices, as well as other ones, in order to make possible many exchanges between teacher and pupil to happen, so that in reading events active cooperation may always happen